Water scarcity in developing countries? - Manuel Schiffler (Deutsches Institut für Entwicklungspolitik (DIE), 1998)
Due to population growth, water is reported to be becoming increasingly scarce throughout the world. Some 1.3 billion people are without access to clean water, and in some regions water wars are already threatening. These reports are well known - but are they also true? The present paper will argue that it is not global water scarcity but policy failure and misallocation of resources that are responsible for the inadequate access to drinking water: Many countries are aiming for national self-sufficiency in staple foods. Some countries in arid areas are subsidizing the expansion of irrigated agriculture, which accounts for roughly 70 % of the world's water consumption. In the cities a good share of water is lost from the water-supply network, and supply failures often occur because public water utilities, which are often poorly managed, are at the end of their financial tether. Many residents of urban slums are not connected to the water-supply network and are thus forced to pay prices to water vendors that are far higher than the subsidized drinking-water tariffs. Water wars are for the most part not genuine conflicts over scarce water but a symptom of deeply rooted historical and political conflicts, while water scarcity presents the occasion, or at best a catalyst, for additional tensions.
Keywords: 330